Variations of Mount Kenya’s glaciers 1993-2004 - Rostom, Raouf; Hastenrath, Stefan (ERDKUNDE, 2007)
A map is presented of Mount Kenya’s glaciers at scale 1:5,000, based on photogrammetric evaluation of purposeflown aerial photography of 01 September 2004. In conjunction with a corresponding map of September 1993, it documents the drastic recession of Mount Kenya’s glaciers over the past eleven years.